Identifikasi Jamur dan Bakteri Pada Plup Proses Fermentasi Biji Kakao - Tandi, Jenifa Arisa; Kundera, I Nengah; Windarsih, Yulia; Alibasyah, Lestari M.P; Ashari, Abdul; Budiarsa, I Made (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to identify the types of fungi and bacteria that play a role in the fermentation process of cocoa beans. This type of research uses an exploratory laboratory method. The samples in this study were fungi and bacteria during the fermentation process of cocoa beans that had been fermented for approximately 3-5 days. The tools used in this study were digital scales, clear plastic boxes, autoclaves, scissors, micropipettes, spoons, label paper, Petri dishes, incubators, glass covers, Bunsen burners, Erlenmeyer flasks, inoculation needles, stirring rods, microscopes, beakers, measuring cups, scales, hot plates, test tubes, spirit lamp, colony counter, aluminum foil, camera, and writing instruments. The materials used in this study were fermented cocoa bean waste samples colonized by fungi and bacteria, Nutrient Agar (NA) medium, Triple Sugar Iron Agar (TSIA) medium, Bacillus Agar Base, distilled water, crystal violet, eosin dye, iodine, alcohol, and safranin. There are five stages in this research procedure, namely sample collection and preparation, media preparation and sample dilution, sample cultivation on general and selective media, Gram staining, and biochemical testing. The results of this study show that the fungi Saccharomyces cerevisiae and Mucor Sp, as well as the bacteria Bacilllus Sp, are involved in the fermentation process of cacao beans.